IMPLEMENTASI KEBIJAKAN RENCANA STRATEGIS PENGEMBANGAN USAHA MICRO PEQUENAS E EMPREZAS (MPEs) DI DISTRIK VIQUEQUE, TIMOR LESTE - Ilario da Cruz; Agus Suryono; Irwan Noor (REFORMASI, 2015)
Abstract: The Implementation plan of micro businesses or Micro Pequenas Empresas (MPEs) development in Timor Leste conducted by the Directorat Geral Industria e Cooperativas, Ministerio do Comercio, Industria e Ambiente. Implementation in Viqueque district based on Ministerial Decree No. 1/2013 article 18 about MPE development plan. The aim of this plan are for creating jobs, increasing economic growth, reduce unemployment and poverty. Research design in this article is qualitative descriptive study and using Edward Model III to analyse. Research Findings show that policy implementation of MPE development is not match with the targets.it is due to insufficient expert staff who implemented plan, the lack of effective communication between policy makers and implementers of strategic plans, and limited resources and infrastructures. The attitude of officials more inclined to political interests than the professionalism. Changing in the bureaucratic structure made lack of leader traction on taking decisions in the implementation of the plan.